K-pop from Local to Global: A Study on Cultural Nationalism in Korean Pop Culture - Koo, Jeung Mo; Koo, Hyun Mo (The Columbia Journal of Asia, 2022)
K-pop has received global attention during the past decades. It already transcended Korean boundaries and has achieved great success in the global market. Contrary to its brilliant achievement, Korean pop culture is stuck in a paradoxical situation. The more transnational it becomes externally, the more nationalistic it becomes internally. Nationalism has buttressed K-pop’s growth, allowing it to venture out of Korea. Inversely, as K-pop makes its progress abroad, Koreans enjoy a boost in self-esteem. The increase in national pride, intertwined with the historical legacies from Japanese colonial rule and the chronic ’west complex’ prevalent in Korean society, is giving rise to distorted cultural nationalism. Cultural nationalism, in turn, is putting brakes on K-pop’s progress, as evidenced in heated online controversies including the “scandal” regarding Japanese idol Sana(TWICE)’s social media post and Korean netizens’ racist remarks toward Thai star Lisa(BLACKPINK). K-pop is currently facing a dilemma as it must multinationalize to further prosper abroad while it should not overlook nationalistic conflicts. Furthermore, K-pop is on the verge of tipping towards cultural imperialism, as cultural supremacy and nationalistic ideals among Koreans are forming a cultural hierarchy. This study sheds light on the cultural nationalism hidden beneath the superficial glamor of K-pop, an issue concerning not only its own future growth but also the ever-present conflict factors in East Asia.